Ultrasound-Assisted Extraction as a First Step in a Biorefinery Strategy for Valorisation of Extracted Olive Pomace - José Carlos Martínez-Patiño; Irene Gómez-Cruz; Inmaculada Romero; Beatriz Gullón; Encarnación Ruiz; Mladen Brnčić; Eulogio Castro (Energies, 2019)
Currently, interest in finding new feedstock as sources of natural food antioxidants is growing. The extracted olive pomace (EOP), which is an agro-industrial residue from the olive pomace extracting industries, is generated yearly in big amounts, mainly in the Mediterranean countries. EOP was subjected to an ultrasound assisted extraction with ethanol-water mixtures. The effect of main parameters, such as ethanol concentration (30−70% v/v), ultrasound amplitude (20−80%), and extraction time (5−15 min), on the extraction of antioxidant compounds was evaluated according to a Box−Behnken experimental design. The antioxidant capacity of the resulting extracts was determined by measuring their content in total phenolic compounds (TPC) and flavonoids (TFC), as well as their antioxidant activity by DPPH, ferric reducing antioxidant power (FRAP), and ABTS assays. Considering the simultaneous maximization of these five responses, the optimal conditions were found to be 43.2% ethanol concentration, 70% amplitude, and 15 min. The ultrasound assisted extraction of EOP under these optimized conditions yielded an extract with a phenolic and flavonoid content (per gram of EOP) of 57.5 mg gallic acid equivalent (GAE) and 126.9 mg rutin equivalent (RE), respectively. Likewise, the values for DPPH, ABTS, and FRAP assay (per gram of EOP) of 56.7, 139.1, and 64.9 mg Trolox equivalent, respectively were determined in the optimized extract.